Spectroscopy of the frustrated quantum antiferromagnet Cs2CuCl4. (28th September 2021) - Fumega, Adolfo O; Wong, D; Schulz, C; Rodríguez, F; Blanco-Canosa, S
Abstract: We investigate the electronic structure of Cs2 CuCl4, a material discussed in the framework of a frustrated quantum antiferromagnet, by means of resonant inelastic x-ray scattering (RIXS) and density functional theory (DFT). From the non-dispersive highly localized dd excitations, we resolve the crystal field splitting of the Cu 2+ ions in a strongly distorted tetrahedral coordination. This allows us to model the RIXS spectrum within the crystal field theory (CFT), assign the dd orbital excitations and retrieve experimentally the values of the crystal field splitting parameters D q, D s and D τ . The electronic structure obtained ab-initio agrees with the RIXS spectrum and modelled by CFT, highlighting the potential of combined spectroscopic, cluster and DFT calculations to determine the electronic ground state of complex materials.